Hybrid PV/T solar systems for domestic hot water and electricity production - Kalogirou, Soteris A.; Tripanagnostopoulos, Yiannis (My University, 2006)
Hybrid photovoltaic/thermal (PV/T) solar systems can simultaneously provide electricity and heat, achieving a higher conversion rate of the absorbed solar radiation than standard PV modules. When properly designed, PV/T systems can extract heat from PV modules, heating water or air to reduce the operating temperature of the PV modules and keep the electrical efficiency at a sufficient level. In this paper, we present TRNSYS simulation results for hybrid PV/T solar systems for domestic hot water applications both passive (thermosyphonic) and active. Prototype models made from polycrystalline silicon (pc-Si) and amorphous silicon (a-Si) PV module types combined with water heat extraction units were tested with respect to their electrical and thermal efficiencies, and their performance characteristics were evaluated. The TRNSYS simulation results are based on these PV/T systems and were performed for three locations at different latitudes, Nicosia (35°), Athens (38°) and Madison (43°). In this study, we considered a domestic thermosyphonic system and a larger active system suitable for a block of flats or for small office buildings. The results show that a considerable amount of thermal and electrical energy is produced by the PV/T systems, and the economic viability of the systems is improved. Thus, the PVs have better chances of success especially when both electricity and hot water is required as in domestic applications.
Keywords: Solar energy; Photovoltaics; Thermal collectors; Hybrid photovoltaic/thermal system; Water heating